Pembangunan dan Implementasi Sistem Informasi Pendaftaran dan Absensi Online Magang Berbasis Website pada BPTU HPT Padang Mengatas - Apri Wenando, Febby; Pratama Santi, Rahmatika; Hubby Aziira, Aina; Wahyuni, Ullya Mega; Dwi Kartika, Afriyanti; Erlangga Adi, Muhammad; Fadwa Shifana, Deyola (LPPM UMRI, 2023)
Balai Pembibitan Ternak Unggul Hijauan Pakan Ternak (BPTU HPT) in Padang Mengatas is the only Livestock Breeding Center in Indonesia that specializes in producing breeding stock of Simental and Limousin beef cattle. While BPTU HPT Padang Mengatas focuses on livestock farming, they also recognize the need for technology and programs to streamline their work and keep up with the evolving times. Currently, various activities such as internship registration, cattle sales, visit requests, guest registration, and community satisfaction indexing are still carried out manually, resulting in significant time consumption for both data entry and report compilation. Specifically, in the internship process, BPTU HPT Padang Mengatas requires the implementation of an internship attendance information system for interns. This system enables evaluation of the interns based on their performance and presence during the internship period. The introduction of this information system is expected to assist the employees of BPTU HPT Padang Mengatas, enabling internship supervisors to expedite the data collection process. Additionally, it is anticipated that this application will facilitate BPTU HPT Padang Mengatas in monitoring and controlling its activities.